Measuring Acceptance of Sleep Difficulties: The Development of the Sleep Problem Acceptance Questionnaire. Issue 11 (1st November 2015) - Bothelius, Kristoffer; Jernelöv, Susanna; Fredrikson, Mats; McCracken, Lance M.; Kaldo, Viktor
Abstract: Study Objectives: Acceptance may be an important therapeutic process in sleep medicine, but valid psychometric instruments measuring acceptance related to sleep difficulties are lacking. The purpose of this study was to develop a measure of acceptance in insomnia, and to examine its factor structure as well as construct validity. Design: In a cross-sectional design, a principal component analysis for item reduction was conducted on a first sample (A) and a confirmatory factor analysis on a second sample (B). Construct validity was tested on a combined sample (C). Setting: Questionnaire items were derived from a measure of acceptance in chronic pain, and data were gathered through screening or available from pretreatment assessments in four insomnia treatment trials, administered online, via bibliotherapy and in primary care. Participants: Adults with insomnia: 372 in sample A and 215 in sample B. Sample C (n = 820) included sample A and B with another 233 participants added. Measures: Construct validity was assessed through relations with established acceptance and sleep scales. Results: The principal component analysis presented a two-factor solution with eight items, explaining 65.9% of the total variance. The confirmatory factor analysis supported the solution. Acceptance of sleep problems was more closely related to subjective symptoms and consequences of insomnia than to diary description of sleep, or to acceptance of general private events. Conclusions: The Sleep Problem Acceptance Questionnaire (SPAQ), containing the subscales "Activity Engagement" and "Willingness", is a valid tool to assess acceptance of insomnia.